Diversity of Anisoptera in Cisuru village, Cilacap Regency, Central Java - Novi Salsabila; Ardyan Pramudya Kurniawan (Jurnal Biologi Tropis, 2023)
Anisoptera is a suborder of Odonata and is a biological wealth that has an important role for the environment. One of the locations that has the potential for Anisoptera diversity is Cisuru Village, Cipari District, Cilacap Regency, Central Java. However, no research has ever been conducted on dragonflies, especially Anisoptera at the site. This study aims to study the abundance and diversity of Anisoptera species, as well as environmental parameters in Cisuru Village, Cilacap, Central Java. Data retrieval using the point count method. The results of the study found 19 species of Anisoptera from 3 families (Aeshnidae, Gomphidae, Libellulidae). The most common species is Orthetrum sabina (Settlements: 153 individuals/0.5 ha; Rice fields: 225 individuals/0.5 ha; and Rivers: 126 individuals/0.5 ha). Anisoptera diversity index (H') values in all three habitats were classified as medium category (Settlement: 2.06; Rice fields: 1.29; and River: 1.63). Anisoptera is mostly found in light intensity conditions of 26,309 ± 17,117 lux; air humidity 37.85% ± 6.2%; and wind speeds of 0.75 ± 0.34 m/s.